„Repatriation“ of Baltic germanies after pacts: new german demografical policy or implementatin of earlier formed plans - Kangeris, Karlis (Genocidas ir rezistencija, 2000)
In his speech in October 1939 in Reichstag, Reich Chancellor Adolf Hitler described the reorganisation of the ethnographic situation in Eastern Europe as “one of the most important tasks”. Emigration, or leaving one’s place of origin or, according to propaganda, “answering the Führer’s call” and “returning home to the Reich”, was one aspect of the ethnic reorganisation. Another aspect of this reorganisation was the problem of finding new residences for ‘German citizens in danger’. These new places of residence could be in the Reich or in any other occupied territory. Therefore, contemporary scholars quite rightly link the beginning of the systematic annihilation of the Jews to the German–Soviet Pact and to the ethnic reorganisation of Eastern Europe. The transfer of Baltic Germans from Estonia and Latvia to the annexed territories in Poland – the new provinces of the German Reich – started this process.
Keywords: German; repatriation; Molotov-Ribbentropp pact; Estonia; Latvia